Negotiating postmodernism - Gabardi, Wayne, 1955- (University of Minnesota Press, 2001)
Joining the modern-postmodern debate, this book suggests that the polarizing polemics of the radical postmodernists who once dominated the discussion have given way to a new "critical postmodernism" characterized by dialogue, accommodation, and synthesis. A comprehensive survey, Negotiating Postmodernism also marks the arrival of a powerful, critical presence on the scene, one that advances the idea of a late modern-postmodern social and cultural transition.